PENGARUH KEGIATAN PERATURAN BARIS BERBARIS (PBB) TERHADAP KEDISIPLINAN ANAK KELOMPOK B DI TK DHARMA WANITA 68 KALIPLOSO CLURING BANYUWANGI - Syamsudin, Moh. Anas; Dwi Sabela, Viorela; Yudha, Firma (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The development of discipline character begins from an early age, especially when children begin to enter preschool education. For early childhood, discipline is one of the most important aspects in the formation of their character and personality. At this time, discipline in children is decreasing, including in Kindergarten Dharma Wanita 68 Kaliploso Banyuwnagi. Therefore, alternative solutions are needed to improve children's discipline. In this study, the practice of marching is used as a means to improve children's discipline at Kindergarten Dharma Wanita 68 Kaliploso Banyuwnagi. The purpose of this study is to determine the influence of marching activities on the discipline of children in group B at Dharma Wanita 68 Kaliploso Banyuwnagi Kindergarten. This type of research is quantitative using a pre-experimental design one-group pretest-posttest. The subjects used in this study were 15 children. The data collection techniques used are observation, interviews, and tests. The data analysis techniques used are normality test and T-test. The results obtained from this study are a significance value showing a result of 0.000 where the value is less than 0.05. Therefore, it can be decided that there is a significant difference between pretest and posttest. It can be concluded that there is an influence between the marching rules and children's discipline.